Balancing water : restoring the Klamath Basin - Blake, Tupper Ansel (University of California Press, 2000)
The Klamath Basin is a land of teeming wildlife, expansive marshes, blue-ribbon trout streams, tremendous stretches of forests, and large ranches in southern Oregon and northern California. Known to waterfowl, songbirds, and shorebirds, the Klamath Basin's marshlands are a mecca for birds along the Pacific Flyway.